Emergy and Form: Accounting Principles for Recycle Pathways - Brown†, Mark T. (Journal of Environmental Accounting and Management, 2026)
A brief exploration of the concept of information is undertaken to parse the different meanings and measures. We agree with Odum (1996) that information might best be expressed as complexity and posit that the shape or form of an object is a type of information and with increasing complexity of form there is a corresponding increase in emergy required to make it. We also agree with Odum that an increase in concentration of a material increases its emergy per mass (i.e. its UEV) and a decrease in concentration as when a material is dispersed requires a decrease in the emergy stored. We present new thoughts related to the emergy in form as distinct from the emergy of the materials that make up the form. We suggest that the emergy of form is lost when the form is consumed, but the emergy of the substance is maintained. We define recycle pathways in such a way as to clarify emergy accounting for products and by-products. These considerations are important when evaluating “circular economies” where products and by-products are recycled once their useful life is finished. This proposed method of dealing with recycled material is a refinement of the emergy accounting procedure.